Stability, preservation and storage of As(iii), DMA, MMA and As(v) in water samples. Issue 28 (24th June 2021) - Brombach, Christoph-Cornelius; Lancaster, Shaun T.; Dexter, Matthew A.; Thompson, K. Clive; Corns, Warren T.
Abstract : Multiple preservation techniques for arsenic speciation in water are tested simultaneously, providing more definitive optimisations of container material, acidification, temperature, and light exposure. Abstract : Correct handling and preservation of water samples is crucial to ensure their integrity for arsenic speciation measurements. ISO TS 19620:2018 is a method for the determination of arsenic(iii ) and arsenic(v ) species in waters by liquid chromatography (LC) coupled to inductively coupled plasma mass spectrometry (ICP-MS) or hydride generation atomic fluorescence spectrometry (HG-AFS). During the development of this method, a study was performed to establish the best practices for storage and preservation of samples to maintain the integrity of the arsenic speciation and stability. Four arsenic species were studied: arsenite (As(iii )), arsenate (As(v )), monomethylarsonic acid (MMA) and dimethylarsinic acid (DMA) in three different water types: deionised water, mineral water and natural river water. The effect of sample bottle material, light, storage temperature, and acidification were evaluated. When samples are acidified and refrigerated, they can reliably be stored for up to 12 weeks without significantly affecting the arsenic concentration and speciation. The sample bottle material and light had no affect on the speciation integrity or stability.